1979
DOI: 10.1111/j.1432-1033.1979.tb13136.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Phenylalanyl‐tRNA Synthetase

Abstract: The localization of the binding sites of the different ligands on the constitutive subunits of yeast phenylalanyl-tRNA synthetase was undertaken using a large variety of affinity and photoaffinity labelling techniques. The tRNAPh' was cross-linked to the enzyme by non-specific ultraviolet irradiation at 248 nm, specific irradiation in the wye base absorption band (315 nm), irradiation at 335 nm, in the absorption band of 4-thiouridine (s"U) residues introduced in the tRNA molecule, or by Schiffs base formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…The experiment exploits the photoreactivity of wybutine (Y-Wye), which occurs in tRNAPhe from yeast at the 3' side of the anticodon (10). The results demonstrate that the orientation of Y-Wye with respect to the mRNA is the same, or at least very similar, before and after translocation.…”
mentioning
confidence: 72%
“…The experiment exploits the photoreactivity of wybutine (Y-Wye), which occurs in tRNAPhe from yeast at the 3' side of the anticodon (10). The results demonstrate that the orientation of Y-Wye with respect to the mRNA is the same, or at least very similar, before and after translocation.…”
mentioning
confidence: 72%
“…Mulvey and Fersht [22] and Baltzinger et al [23] have shown that certain monomeric and tetrameric enzymes act functionally as dimers. Thus, it is possible that the monomeric arginyl-tRNA synthetase is functional as a tRNA"rgdependent dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, earlier binding studies showed that UV irradiation of various (enzyme, tRNAPhe) complexes always led to an exclusive covalent labelling of the fi subunit: for instance s4U-tRNAPhe could be joined top and this suggests the existence of several contact areas between the protein and the ligand since s4U-tRNAPhe contained 5 to 6 modified uridines statistically distributed along the nucleotide sequence; apparently the interaction between ,& and this modified tRNA did not involve the 3 ' end and the catalytic site because no loss of ATP-PPi exchange activity was observed after photoirradiation of the complex [12].…”
Section: Identification Of the Limited Cleavage Sitementioning
confidence: 99%
“…This sequence is part of the fl' domain of p and it must be located near or in the active site. Indeed labelling this lysine resulted in a complete loss of the aminoacylation activity whilst the ATP-PPi exchange reaction remained unaffected [12]. It is worth stressing that this lysine 325 of p is located between two regions of high homology with the small subunit of phenylalanyl-tRNA synthetase from E. coli [ 141.…”
Section: Identification Of the Limited Cleavage Sitementioning
confidence: 99%
See 1 more Smart Citation